Nucleotide Excision Repair Factor XPC Ameliorates Prognosis by Increasing the Susceptibility of Human Colorectal Cancer to Chemotherapy and Ionizing Radiation - Hu, Liang-Bo; Chen, Yin; Meng, Xiao-Dong; Yu, Pan; He, Xu; Li, Jie (Frontiers in Oncology, 2018)
Nucleotide excision repair (NER)is a DNA damage repair mechanism in mammals, but the relationship between NER and human colorectal cancer(HRC) progression has not been clarified yet. In this study,the expression of the NER genes XPA, XPC, XPF, XPG, ERCC1, and XPD was measured in normal and cancerous human colorectal tissue. Among them, only the XPC gene expression was significantly increased in colorectal cancer tissue. To establish the role of XPC in colorectal cancer, small interference RNA (siRNA) targeting XPC was used to knockdown the expression of XPC in HRC cell lines. In addition,an expression vector plasmid containing the XPC cDNA was constructed and stably transfected into HRC cell lines to overexpress the XPC gene. Interestingly, MTT and apoptosis assay demonstrated that XPC gene overexpression significantly increased the susceptibility of HRC cell lines to cisplatin and X-ray radiation. In order to study the relationship between XPC expression and the progression of HRC, XPC expression was measured in 167 patients with colorectal cancer. The results showed that patients with high XPC expression had longer survival time. Cox regression analysis showed that high XPC expression might be a potential predictive factor for colorectal cancer. In conclusion, XPC plays a key role in the susceptibility of colorectal cancer to chemotherapy and ionizing radiation and is associated with a good patients’ prognosis.